Drought impacts mineral contents in Andean Potato cultivars - Lefevre, I.; Ziebel, J.; Guignard, C.; Hausman, J.F.; Gutiérrez Rosales, R.O.; Bonierbale, Merideth W.; Hoffmann, L.; Schafleitner, R.; Evers, D. (Wiley, 2012)
Mineral micro‐ and macronutrients in tubers of 21 Andean potato cultivars were investigated in a field trial under control and drought conditions. Mineral concentrations in potato tubers were highly variable between genotypes; some were significantly and positively correlated with each other, the most noteworthy associations being Na–Ca, Mn–Mg and Zn–Fe, in both control and drought‐stressed plants. Overall, increasing yields are related to decreased concentrations of some nutrients, albeit some higher‐yielding cultivars also displayed important concentrations of nutrients in their tubers. The most striking result was the increase in the concentration of the majority of the analysed cations in a large number of cultivars in response to water depletion; some of them, such as K, may be related to water homeostasis and/or to sucrose loading and unloading in phloem sap. Tuber mineral concentrations were not related to drought tolerance in terms of tuber productivity. Interestingly, yield loss under drought was not correlated with yield potential under control conditions. Identification of cultivars such as 703264 and 701106 able to maintain good yield stability in association with high mineral contents under water deprivation is of particular interest, especially in view of the importance of potato as a staple crop and the expansion of its cultivation to non‐optimal cultivation areas in the context of changing climatic conditions.